젊은 환자에서 장기간의 클로나제팜 복용 후 발생한 백내장 1예 - 주병주, 강용석, 김태진, 박정현Byung Ju Choo MD Young Suk Kang MD Tai Jin Kim MD Jung Hyun Park MD (Daihan angwa haghoi jabji, 2011)
목적: 젊은 환자에서 클로나제팜의 장기 복용 후 항정신성약으로 인한 수정체 혼탁과 유사한 양상의 백내장 소견이 발생한 증례를경험하였기에 이를 보고하고자 한다. 증례요약: 37세 여자가 양안 시력저하를 주소로 내원하였다. 교정 시력은 우안 0.8, 좌안 0.6이었고, 세극등 검사상 양안 피질 백내장소견이 발견되었으며 다른 안과적 이상은 발견되지 않았다. 백내장의 위험인자에 대하여 환자의 과거력, 약물력, 가족력 등에 대해알아본 결과, 과거력상 20년 전부터 원인불명의 무도병(chorea) 진단하에 신경과에서 클로나제팜(0.5-1 mg/일)을 복용하고 있었다. 그 외 백내장을 유발한다고 알려져 있는 약제를 장기 복용한 과거력은 없었다. 결론: 클로나제팜이 백내장을 유발하였을 가능성이 있으므로 장기간 복용 중에는 규칙적인 안과 검진이 필요할 것으로 생각한다. Purpose: To report a case of cataract after long-term use of clonazepam in a young patient, with a similar appearance to cataract induced by other psychotropic agents. Case summary: A 37-year-old woman complained of a visual disturbance in both eyes. The best-corrected visual acuity was 0.8 in the right eye and 0.6 in the left eye. Bilateral cortical cataract was observed on slit-lamp examination, and no other ophthalmic abnormalities were found. Potential risk factors for cataract were investigated, including past medical and family history, revealing a 20-year history of oral clonazepam (0.5-1 mg/day), for the neurological diagnosis of “chorea of unknown etiology”. Detailed medication history did not reveal long-term use of any other drugs which could have induced the cataract. Conclusions: Because clonazepam use may induce cortical cataract, regular ophthalmologic examinations are necessary during long-term oral psychotropic therapy. KCI Citation Count: 0